2019
DOI: 10.1007/s10729-019-09468-2
|View full text |Cite
|
Sign up to set email alerts
|

Individuals’ adoption of smart technologies for preventive health care: a structural equation modeling approach

Abstract: Healthcare is moving towards new patterns and models, with an increasing attention paid to prevention. Smart technologies for mobile health care are emerging as new instruments to monitor the state of essential parameters in citizens. A very debated subject in literature is the critical role played by citizens' acceptance and willingness to pay for mobile health technologies, especially whereas the services provided are preventive rather than curative. The adoption of such technologies is, indeed, a necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 76 publications
6
73
0
1
Order By: Relevance
“…Overall, there are several other studies all of which establish the relevance of TAM (particularly PEOU and PU) in the online learning context ( Estriegana et al, 2019 , Gahtani, 2016 , Revythi and Tselios, 2019 , Salloum et al, 2019 , Millat et al, 2018 ). Apart from online learning, TAM has also been used to predict the adoption intention in various other contexts like smart-homes ( Pal et al, 2018 , Park et al, 2018 ), smart products ( Dutot et al, 2019 , Pal et al, 2020 ), smart healthcare ( Bettiga et al, 2020 , Kamal et al, 2020 ), music streaming services ( Pal and Triyason, 2018 , Fernandes and Guerra, 2019 ), and many more.…”
Section: Related Workmentioning
confidence: 99%
“…Overall, there are several other studies all of which establish the relevance of TAM (particularly PEOU and PU) in the online learning context ( Estriegana et al, 2019 , Gahtani, 2016 , Revythi and Tselios, 2019 , Salloum et al, 2019 , Millat et al, 2018 ). Apart from online learning, TAM has also been used to predict the adoption intention in various other contexts like smart-homes ( Pal et al, 2018 , Park et al, 2018 ), smart products ( Dutot et al, 2019 , Pal et al, 2020 ), smart healthcare ( Bettiga et al, 2020 , Kamal et al, 2020 ), music streaming services ( Pal and Triyason, 2018 , Fernandes and Guerra, 2019 ), and many more.…”
Section: Related Workmentioning
confidence: 99%
“…the doctor opinion. Adoption of technology for preventive healthcare, indeed, is not only pushed by individual beliefs, but is motivated by social pressure as well [5,21]. This focus could also improve our understanding of the healthcare systems in the adoption processes of these technologies.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Hence, both practitioners and academics show a growing interest in understanding the influential factors that explain a continued adoption of these technologies for lifestyle monitoring [3]. Technology adoption processes, indeed, represent a fundamental piece of knowledge to favour the diffusion of innovation [4] especially where such a diffusion may support the adoption of virtuous practices by users [5], as in the case of wearables. In contexts in which public healthcare systems are exposed to budgetary constraints, disease prevention, also through the support to functional, healthy conducts and lifestyles becomes of the essence to ensure welfare sustainability [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a relevant study, it was observed that self-monitoring of personal mood with a mobile application reduces symptoms related to depression and anxiety and improves emotional well-being [21]. Consequently, mobile applications may be used as preventive medical tools in a multitude of ways [2,10,14].…”
Section: Plos Onementioning
confidence: 99%
“…This phenomenon is expected to lead to congestion in healthcare systems and higher healthcare costs. Consequently, preventive measures that can lead to a healthier life even at a later age emerge as a likely solution [1,2]. Given the recent Covid-19 pandemic, the fragility of the healthcare systems worldwide has become more evident.…”
Section: Introductionmentioning
confidence: 99%